Distribution Frequency of Pathogenic Bacteria Isolated from Cutaneus Leishmaniasis Lesions - Ziaei, Hengameh (The Korean Society for Parasitology, 2008)
Cutaneous leishmaniasis (CL) is a parasitic disease characterized by single or multiple ulcerations. Secondary bacterial infections are one of the complications that can increase the tissue destruction and the resulting scar. To better determine the incidence of real secondary bacterial infections in CL, we designed the current study. This was a cross-sectional study performed in Skin Diseases and Leishmaniasis Research Centre, Isfahan, Iran. A total of 1,255 patients with confirmed CL enrolled in the study. Sterile swaps were achieved for ulcer exudates and scraping was used for non-ulcerated lesions. All samples were transferred to tryptic soy broth medium. After 24 hr of incubation at 37℃ they were transferred to eosin methylene blue agar (EMB) and blood agar. Laboratory tests were used to determine the species of bacteria. Among 1,255 confirmed CL patients, 274 (21.8%) had positive cultures for secondary bacterial infections. The bacteria isolated from the lesions were Staphylococcus aureus in 190 cases (69.3%), coagulase negative Staphylococcus in 63 cases (23.0%), E. coli in 10 cases (3.6%), Proteus sp. in 6 cases (2.2%), and Klebsiella sp. in 5 cases (1.9%). The results show that the overall incidence of secondary bacterial infections in the lesions of CL was 21.8%, considerably high. The incidence of secondary bacterial infections was significantly higher in ulcerated lesions compared with non-ulcerated lesions.